2002
DOI: 10.1002/sia.1161
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion properties on nanometric scale of silicon oxide and silicon nitride surfaces modified by 1‐octadecene

Abstract: Silicon oxide and silicon nitride surfaces have been treated with 1-octadecene at ∼200• C . The resulting film topography has been inspected by atomic force microscopy (AFM), showing a densely packed organic coating with a corrugation of some tenths of a nanometre. High-mass-resolution time-of-flight secondary ion mass spectrometry (ToF-SIMS) spectra from such surfaces display octadecene-as well as substraterelated peaks. Furthermore, peaks diagnostic of the formation of SiOC or SiC linkages are observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
3
14
1
1
Order By: Relevance
“…These Pt at % values are comparable to those for non-chemically treated, dielectric reference samples in the same ALD run. We note that, in contrast to our observations, previous studies have reported that 1-octadecene can chemisorb onto SiO 2 and Si 3 N 4 surfaces, [14,15] However, a subsequent spectroscopic study showed that those results might be due to the existence of SiH x sites after surface treatment, leaving the surface with reactive groups like those present on bare silicon instead of only SiO 2 or Si 3 N 4 . [16] In our study, we used piranha treatment before HF etching and this hydroxylated the hydrophilic dielectric surface.…”
contrasting
confidence: 99%
“…These Pt at % values are comparable to those for non-chemically treated, dielectric reference samples in the same ALD run. We note that, in contrast to our observations, previous studies have reported that 1-octadecene can chemisorb onto SiO 2 and Si 3 N 4 surfaces, [14,15] However, a subsequent spectroscopic study showed that those results might be due to the existence of SiH x sites after surface treatment, leaving the surface with reactive groups like those present on bare silicon instead of only SiO 2 or Si 3 N 4 . [16] In our study, we used piranha treatment before HF etching and this hydroxylated the hydrophilic dielectric surface.…”
contrasting
confidence: 99%
“…These surface free energies matched closely the results obtained from contact angle measurements on these SAMs. Organic coating of silicon oxide and silicon nitride by 1-octadecene decreased the surface energies by a factor of $1.5 as deduced from adhesion force measurements and contact angles [384].…”
Section: Determination Of Hamaker Constants Adhesion and Surface Enementioning
confidence: 89%
“…Derivatization techniques exploit the reactivity of the surface silicon-hydrogen (Si-H x ) or Si-N bonds. In the first case, silicon nitride is modified with long chain alkenes or alkynes by thermal (Pignataro et al, 2002;Arafat et al, 2004Arafat et al, , 2007 or photochemical activation (Coffinier et al, 2007). Regarding reactivity through the Si-N-H moieties on silicon nitride surfaces, Karymov et al (1995) modified chemical surfaces with halogen derivatives of ethane and propane; further covalent bonding with the DNA base amino group requires heating at 65 • C, so, a general application is not possible since most proteins undergo thermal denaturation.…”
Section: Introductionmentioning
confidence: 99%